Soft tissue facial profile analysis of adult Iraqis with different classes of malocclusion - Shahbaa A Mohammed; Layth M K Nissan; Shaymaa S Taha (College of Dentistry/ University of Baghdad, 2013)
Background: Complete analysis of facial profile should also include an evaluation of soft tissue morphology. Materials and Method:The sample consisted of 90 Iraqi adults (45 males and 45 females) aged 18-25 years from Baghdad city divided into 3 groups according to the ANB angle with 30 subjects in each group (15 males and 15 females) for class I, II and III. Lateral cephalometric radiograph was taken for each subject and 8 angular and 5 linear measurements were identified and determined, t-test, ANOVA and LSD test were used to compare between both genders and between different classes. Results:Showed that females had greater angular measurements and smaller linear measurements with more lip prominence than males in all classes, there was more convex facial profile with more prominent forehead, more prominent tip of the nose with increased facial heights and more prominent lips in class II subjects than in class I and IIIsubjects. Conclusion: There is wide variation in soft tissue facial profile among different classes of malocclusion and careful determination of the components of soft tissue facial profile is very important in the diagnosis and treatment planning.